2016
DOI: 10.1111/tme.12377
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinical coding data to determine causes of critical bleeding in patients receiving massive transfusion: a bi‐national, multicentre, cross‐sectional study

Abstract: Algorithms using ICD codes can determine the cause of critical bleeding in patients requiring MT with good to excellent agreement with clinical history. DRG are less suitable to determine critical bleeding causes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…From 95 publications initially identified, 52 were excluded either because they did not include a gold standard data source, used administrative claims data as the gold standard, or otherwise did not meet our criteria for inclusion. A total of 43 studies from six countries were identified (Table ). Of these, 72.1% ( n = 31) were published within the last 5 years (ie, since 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From 95 publications initially identified, 52 were excluded either because they did not include a gold standard data source, used administrative claims data as the gold standard, or otherwise did not meet our criteria for inclusion. A total of 43 studies from six countries were identified (Table ). Of these, 72.1% ( n = 31) were published within the last 5 years (ie, since 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the quality of published studies varied. Seven studies used both medical records as a gold standard and a full set of validity measures. These were multiple institution studies published mainly from Australia ( n = 3) and Japan ( n = 2).…”
Section: Type Of Outcomes Validatedmentioning
confidence: 99%
“…Bleeding context was categorized using the diagnostic and procedure codes into 10 categories: (1) trauma; (2) cardiothoracic surgery, (3) vascular surgery, (4) cardiothoracic surgery plus vascular surgery, (5) liver transplant, (6) gastrointestinal hemorrhage, (7) gastrointestinal hemorrhage plus surgical bleed, (8) other surgery, (9) medical/other, and (10) obstetric hemorrhage. Details on the categorization of bleeding contexts have been previously published 30 …”
Section: Methodsmentioning
confidence: 99%
“…The ANZ‐MTR contains data for patients ≥18 years of age who received a MT, defined as ≥5 red blood cell units within a 4‐h period for any bleeding context . MT cases in the registry have been algorithmically categorized into broad groups of critical bleeding events as previously described . In summary, the critical bleeding categories include trauma, obstetrics, surgical bleeding (cardiothoracic, vascular, liver, other surgery), GIB, cases with both GIB and surgical bleeding, and other medical conditions.…”
Section: Methodsmentioning
confidence: 99%